Rich and great: studies in honour of Anthony J. Spalinger on the occasion of his 70th Feast of Thoth - Landgráfová, Renata; Mynářová, Jana (Charles University in Prague, Faculty of Arts, 2016)
"Professor Spalinger's scholarship spans [...] from the Old Kingdom down to the Late Period. The subjects on which he has published range from problems connected with the Egyptian army and military documents to literature, narrative strategies in royal inscriptions and monumental relief decoration. He has sudied Egyptian calendrics and rituals connected with feasts in great detail. [...] The articles assembled in the present volume reflect Tony's wide range of interests"-- Page 7
Festschrift for Professor Anthony Spalinger, University of Auckland Dept. of Classics and Ancient History. - Includes bibliographical references and index
Keywords: Festschrift; Aufsatzsammlung; Kultur; Ägypten